A priori determination of the elastic and acoustic responses of periodic poroelastic materials. (1st December 2020) - Deshmukh, Sagar; Borkar, Ankush; Alankar, Alankar; Krishnan, Shankar; Ramamoorthy, Sripriya
Abstract: Designed periodic foam structures have the potential for achieving predictable acoustic performance. For foam structures that have small strand thickness and made of low-modulus material, rigid-porous assumption may be inaccurate owing to strong fluid-structure coupling. The goal of this study is to design and predict the elastic and acoustic responses of periodic poroelastic structures. Three surface based and one truss based unit cell configurations are considered for study. Elastic properties of these unit-cell configurations are estimated using the homogenization approach and validated experimentally. The predicted elastic properties are used along with the predicted five microscopic Johnson-Champoux-Allard (JCA) parameters for estimating the response of periodic foam structures using the Biot-UP formulation. Parametric study reveals that the effect of structural modes on acoustic absorption coefficient increases with increase in porosity as well as with decrease in pore size. A soft porous periodic lattice sample is fabricated and its predicted absorption coefficient as well as sound-induced displacement response are experimentally validated. The approach presented here will be useful to design soft periodic foam structures for desired structural and acoustic response, and to control the effect of structural modes on acoustic response.